Analisis Teknis Produksi Bioetanol dan Potensi Daya Listrik Dengan Memanfaatkan Limbah Singkong: Technical Analysis of Bioethanol Production and Electrical Power Potential By Utilizing Cassava Wastea - Hariyadi, Tiara Puja (Indonesian Journal of Electrical Engineering and Renewable Energy (IJEERE), 2022)
Cassava production in Riau Province has bioethanol potential which is quite capable as a substitute for fossil fuels. Bioethanol is an alternative and environmentally friendly energy that can be used as a fuel mixture for generator sets. One of the highest sources of raw material for bioethanol production is the cassava plant. Waste originating from cassava dregs and peels is still not fully utilized, even though this waste contains carbohydrates which can be converted into ethanol. Based on the content derived from cassava itself, it has a starch content of 35% which contains amylose and amylopectin which can be converted into ethanol. The method used in this research is descriptive research with biochemical conversion. This study aims to determine the electrical potential generated by bioethanol from cassava waste so that it is expected to reduce the use of fossil fuels. To determine the level of ethanol produced, it can be done by simulating it in the SuperPro software. The steps taken to produce bioethanol are pre-treatment, hydrolysis, fermentation, and purification, from the total production of cassava as much as 203,417 tons / year, 25,683 kg / hour of cassava will be used with 1093.4 L / day of bioethanol. The 100% power potential without a gasoline mixture is 266.75 kW, while 10% ethanol with a mixture of 90% gasoline is 402.79 kW.